Observations sur le regime de la salinite des eaux marines dans la zone sud du littoral roumain de la mer noire dans les conditions specifiques de l’annee 1970 - Șerpoianu, Gheorghe; Machitescu, Adriana; State, Georgeta (Cercetări Marine - Recherches Marines, 2026)
The authors present in the paper the features of the marine water salinity regime in the south part of the Black Sea Romanian littoral, in the 1970 year with unusual high flow of the Danube River. On the basis of the observations carried out dally in the shallow water near Constantza, and mouthy, off shore on the East Constantza profile, 30 Nautical miles for from the shore, it is show that the strongest influence of the Danube fresh water have been registered In the July - September period in the shallow zones and In the May-September period the off sea zones. The minimum values of the salinity registered during the 1970s in the 0-30 m water column were much smaller than the smallest values known until today, fact which attest this influence exerted by the big flow of the Danube river - 1970.